La “guerra” en la jurisprudencia de la Corte Interamericana de Derechos Humano (2010)
How have Inter-American Human Rights bodies dealt with the notion of “war”, which has been transformed over time into the notion of internal and international “armed conflicts”? This question provides the analytical foundation of the first part of this study, which sets out the various types of conflicts that have occurred in the American continent. These situations (armed conflicts, internal strife, State terrorism) have produced a wide range of legal categorizations, utilized by both the Commission and Inter-American Court of Human Rights in their case-law. This conceptual delimitation carried out by these two bodies is all the more important as it affects the law that applies to armed conflicts. Indeed, by analysing this question, the never-ending debate on the relationship between International Human Rights Law and International Humanitarian Law reappears. The second part of this study therefore focuses on the issue of discovering whether and in which way jus in bello has found its place into the Inter-American Human Rights bodies’ case-law. As the active political life of Latin American societies has shown, the study of the different applicable legal regimes also requires looking into “state of emergency” Law, an issue which has been shaped by the Inter-American Court and Commission’s work.